Multi-scale modeling of electron beam melting of functionally graded materials. (15th August 2016) - Yan, Wentao; Ge, Wenjun; Smith, Jacob; Lin, Stephen; Kafka, Orion L.; Lin, Feng; Liu, Wing Kam
Abstract: Electron Beam Melting (EBM) is a promising powder-based metal Additive Manufacturing (AM) technology. This AM technique is opening new avenues for Functionally Graded Materials (FGMs). However, the manufacturing process, which is largely driven by the rapidly evolving temperature field, poses a significant challenge for accurate experimental measurement. In this study, we develop a novel multi-scale heat transfer modeling framework to investigate the EBM process of fabricating FGMs. Our heat source model mechanistically describes heating phenomena based on simulation of micro-scale electron-material interactions. It is capable of accounting for the material properties and electron beam properties that depend on experimental setup. The heat source model is utilized in the thermal evolution model of individual powder particles at the meso-scale to elucidate the melting and coalescing processes for mixed powder particles of different materials and different sizes. Another meso-scale simulation is conducted to evaluate the effective thermal conductivity of the original powder bed for the macro-scale model. A macro-scale heat transfer model is developed, in which the coalescence state is tracked to determine the effective material properties of the powder bed. Predictions of molten pool size are compared against published experimental results for validation. Graphical abstract: In this study, we develop a novel multi-scale heat transfer modeling framework to investigate the EBM process of fabricating FGMs. Our heat source model is based on micro-scale electron-material interaction simulations. It is capable of accounting for the material properties and electron beam properties that are dependent on experimental setup. The heat source model is utilized in the thermal evolution model of individual powder particles at the meso-scale to elucidate the melting and coalescing processes for mixed powder particles of different materials and different sizes. Another meso-scale simulation is conducted to evaluate the effective thermal conductivity of the original powder bed for the macro-scale model. A macro-scale heat transfer model is developed, in which the coalescence state is tracked to determine the effective material properties of the powder bed. Predictions of molten pool size are compared against published experimental results for validation.